2023
DOI: 10.1590/1517-8692202329012022_0278
|View full text |Cite
|
Sign up to set email alerts
|

Strength Training of Long Jump Athletes

Abstract: Introduction Lower limb strength training is one of the daily exercises of jumpers. Heavy squats are a standard method of lower body strength training. The squat is the only compound movement that directly trains “hip strength.” Objective This study aimed to analyze the effect of weighted squats on lower body strength training in long jumpers. Methods 20 jumpers were selected and randomly divided into a general training group and a weighted squat group. Then, the changes in standing triple jump, lateral jump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(10 reference statements)
0
0
0
Order By: Relevance
“…The explosive power of the muscles plays a very important role in movement. Improving explosive power training is the top priority for our long jumpers (Zong, 2023). The long jump consists of 4 phases: running phase, take-off phase, flight phase and landing phase (Kamnardsiria et al, 2015;Alwan et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The explosive power of the muscles plays a very important role in movement. Improving explosive power training is the top priority for our long jumpers (Zong, 2023). The long jump consists of 4 phases: running phase, take-off phase, flight phase and landing phase (Kamnardsiria et al, 2015;Alwan et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, plyometric training was found to improve performance in track and field jumpers [16]. Furthermore, it is suggested that long jumpers should develop their explosiveness using a variety of squat weight-bearing exercises similar to the specific kinetic and kinematic patterns that correspond to their technique [17]. Thus, bilateral plyometric exercises are suggested to be included in the LJ strength and conditional program, especially for the maintenance and/or improvement of strength and power during the off-season training [18].…”
Section: Introductionmentioning
confidence: 99%